Beyond barriers and borders: Digital literacy support for English language learners via communities of practice - Kim, Yeweon; Harding, Alison; Behre, Jane Ingram; Sim, Uhjin; Subramaniam, Mega (Information Research an international electronic journal, 2025)
Introduction: English remains the dominant language on the Internet, exacerbating the digital divide for non-English-speaking populations. It is imperative that these barriers to using the Internet be lessened through adequate and appropriate digital literacy (DL) support. Objective: This study identifies common types of DL learners among English language learners (ELLs), whose first language is Spanish, while also exploring the constraints and opportunities for DL development within this group. Method: We use data obtained through semi-structured interviews with residents of Maryland (US) who identify as Spanish-speaking ELLs. Findings: We find that this group is likely to be forced to acquire DL because of societal pressures, rather than pursuing it as a genuine desire to become digitally competent. In seeking help to navigate difficulties with digital transactions, they often rely on knowledgeable family members but also recognise the value of participating in formal and accessible DL education programmes. However, language barriers to obtaining learning resources, coupled with financial and time constraints and a lack of trusted support systems, pose challenges to their DL acquisition. Conclusion: We conclude with suggestions for strategies grounded in the principles of communities of practice (CoPs) to deliver more tailored DL interventions for ELLs.